Molecular Characteristics of Jujube Yellow Mottle-Associated Virus Infecting Jujube (Ziziphus jujuba Mill.) Grown at Aksu in Xinjiang of China - Jiashu Guo; Yanxiang Wang; Guoping Wang; Jian Hong; Zuokun Yang; Jianyu Bai; Ni Hong (Viruses, 2020)
Chinese jujube (Ziziphus jujuba Mill.) is a native fruit crop in China. Leaf mottle and dapple fruit disease is prevalent in cultivated jujube plants grown at Aksu in Xinjiang Uygur Autonomous Region of China. Jujube yellow mottle-associated virus (JYMaV), a tentative member in the genus Emaravirus, was recently identified from mottle-diseased jujube plants grown in Liaoning Province in China, but its incidence and genetic diversity in China is unknown. In this study, the genome sequences of three JYMaV isolates from two jujube cultivars and one jujube variant were determined by high-throughput sequencing (HTS) for small RNA and rRNA-depleted RNA coupled with RT-PCR assays. Comparison of these sequences together with sequences of the viral RNA segments derived by primer set 3C/5H-based RT-PCR revealed that genetic diversity was present in the virus populations and high sequence variation occurred at the non-translational regions of each of the viral genomic segments. Field investigation confirmed the close association of the virus with leaf mottle symptoms of jujube plants. Furthermore, this study revealed that P5 encoded in the viral RNA5 displayed a nuclear localization feature differing from the plasmodesma (PD) subcellular localization of the virus movement protein (P4), and the two proteins could interact with each other in the BiFC assays. Our study provides a snapshot of JYMaV genetic diversity in its natural hosts.